2009
DOI: 10.1159/000218008
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Vascular Endothelial Growth Factor C Level Is Related to Peritoneal Dialysis Ultrafiltration

Abstract: Background: Local inflammation and neovascularization have a negative influence on peritoneal dialysis (PD). Patients with higher peritoneal transport have higher interleukin-6 (IL-6) and vascular endothelial growth factor-A (VEGF-A) levels in their dialysate. However, the relationship of other members of the VEGF family, such as VEGF-C, to peritoneal transport or ultrafiltration (UF) is yet to be studied. Methods: Peritoneal cytokine and growth factor levels were determined during the peritoneal equilibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Our data are consistent with the recent report by Yang et al, 41 which showed that VEGF-C could possibly be a biomarker for UFF; however, unlike our study, they did not investigate lymphangiogenesis. Our studies of human peritoneal membranes showed that VEGF-C, LYVE-1, and podoplanin mRNA expression were higher in UFF peritoneum than control membranes and that the expression level of VEGF-C and the number of lymphatic vessels correlated with one another.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are consistent with the recent report by Yang et al, 41 which showed that VEGF-C could possibly be a biomarker for UFF; however, unlike our study, they did not investigate lymphangiogenesis. Our studies of human peritoneal membranes showed that VEGF-C, LYVE-1, and podoplanin mRNA expression were higher in UFF peritoneum than control membranes and that the expression level of VEGF-C and the number of lymphatic vessels correlated with one another.…”
Section: Discussionsupporting
confidence: 93%
“…Vascular endothelia growth factor and bFGF, respectively, played an important role in the process of peritoneal angiogenesis and fibrosis. As reported, both of them have correlated with the peritoneal ultrafiltration functions 8,9 . Jiangzi et al 10 .…”
Section: Discussionmentioning
confidence: 86%
“…In this study, we first explored whether the CTGF concentration was positively correlated with the VEGF-C concentration in human PD effluents. Both CTGF and VEGF-C protein in human dialysate are correlated with peritoneal permeability 13,18,37 , suggesting that both could be biomarkers and therapeutic targets for UFF. The dialysate protein level is affected by local peritoneal production and transfer from the blood circulation, which is also dependent on several factors including the plasma level 38 , peritoneal protein clearance 39 , molecular weight with degradation 18 , and protein charge 40 .…”
Section: Discussionmentioning
confidence: 99%